A content validity evaluation of the PEDI-CAT Speedy Mobility domain. - Dumas, Helene M.; Fragala-Pinkham, Maria A.; Rosen, Elaine L.; Ni, Pengsheng (Physiotherapy Theory & Practice, 2021)
Objective: To evaluate the content validity of the PEDI-CAT Speedy Mobility domain through analysis of item and content area exposure, score range and scoring precision. Methods: Retrospective analysis of 3,364 items from assessments (n = 301) completed from 2013 to 2017. Content validity was appraised through analysis of item and content area exposure (item, content area, response frequency), score range (floor and ceiling effect) and scoring precision (person fit, score reliability, item information function). Results: Sixty-five of the 75 general mobility items from the PEDI-CAT Mobility domain item bank were exposed. "Stands up from the middle of the floor" (68%) was the most frequently exposed non-mandatory item. Almost half (49%) of all items were from the Basic Mobility and Transfers content area. Scaled scores ranged from 26.77 to 69.40 with a floor (scores ≤27; n = 51, 17%) but no ceiling effect. Person fit statistics were acceptable for 238 (79%), suggesting limited outliers. Score reliability was sufficient with 68% of scores above threshold (>0.9). Item information function plot indicated less discriminating items at the lower end of the score range. Conclusion: Content is adequately and reliably measuring the intended construct, but additional items at the lower end of the scale could improve score precision.